A Glycine-Rich RNA-Binding Protein, CsGR-RBP3, Is Involved in Defense Responses Against Cold Stress in Harvested Cucumber (Cucumis sativus L.) Fruit - Wang, Bin; Wang, Guang; Shen, Fei; Zhu, Shijiang (Frontiers in Plant Science, 2018)
Plant glycine-rich RNA-binding proteins (GR-RBPs) have been shown to play important roles in response to abiotic stresses in actively proliferating organs such as young plants, root tips, and flowers, but their roles in chilling responses of harvested fruit remains largely unknown. Here, we investigated the role of CsGR-RBP3 in the chilling response of cucumber fruit. Pre-storage cold acclimation at 10oC (PsCA) for 3 d significantly enhanced chilling tolerance of cucumber fruit compared with the control fruit that were stored at 5oC. In the control fruit, only one of the six cucumber CsGR-RBP genes, CsGR-RBP2, was enhanced whereas the other five, i.e. CsGR-RBP3, CsGR-RBP4, CsGR-RBP5, CsGR-RBP-blt801, and CsGR-RBP-RZ1A were not. However, in the fruit exposed to PsCA before storage at 5oC, CsGR-RBP2 transcript levels were not obviously different from those in the controls, whereas the other five were highly upregulated, with CsGR-RBP3 the most significantly induced. Treatment with endogenous ABA and NO biosynthesis inhibitors, tungstate and L-nitro-arginine methyl ester, respectively, prior to PsCA treatment, clearly downregulated CsGR-RBP3 expression and significantly aggravated chilling injury. These results suggest a strong connection between CsGR-RBP3 expression and chilling tolerance in cucumber fruit. Transient expression in tobacco suggests CsGR-RBP3 was located in the mitochondria, implying a role for CsGR-RBP3 in maintaining mitochondria-related functions under low temperature. Arabidopsis lines overexpressing CsGR-RBP3 displayed faster growth at 23oC, lower electrolyte leakage and higher Fv/Fm ratio at 0oC, and higher survival rate at -20oC, than wild-type plants. Under cold stress conditions, Arabidopsis plants overexpressing CsGR-RBP3 displayed lower reactive oxygen species levels, and higher catalase and superoxide dismutase expression and activities, compared with the wild-type plants. In addition, overexpression of CsGR-RBP3 significantly upregulated nine Arabidopsis genes involved in defense responses to various stresses, including chilling. These results strongly suggest CsGR-RBP3 plays a positive role in defense against chilling stress.